Hepatitis C virus‐induced myeloid‐derived suppressor cells regulate T‐cell differentiation and function via the signal transducer and activator of transcription 3 pathway. Issue 4 (22nd June 2016) - Ren, Jun P.; Zhao, Juan; Dai, Jun; Griffin, Jeddidiah W. D.; Wang, Ling; Wu, Xiao Y.; Morrison, Zheng D.; Li, Guang Y.; El Gazzar, Mohamed; Ning, Shun B.; Moorman, Jonathan P.; Yao, Zhi Q.
Summary: T cells play a pivotal role in controlling viral infection; however, the precise mechanisms responsible for regulating T‐cell differentiation and function during infections are incompletely understood. In this study, we demonstrated an expansion of myeloid‐derived suppressor cells (MDSCs), in particular the monocytic MDSCs (M‐MDSCs; CD14 + CD33 + CD11b + HLA‐DR −/low ), in patients with chronic hepatitis C virus (HCV) infection. Notably, HCV‐induced M‐MDSCs express high levels of phosphorylated signal transducer and activator of transcription 3 (pSTAT3) and interleukin‐10 (IL‐10) compared with healthy subjects. Blocking STAT3 signalling reduced HCV‐mediated M‐MDSC expansion and decreased IL‐10 expression. Importantly, we observed a significant increase in the numbers of CD4 + CD25 + Foxp3 + regulatory T (Treg) cells following incubation of healthy peripheral blood mononuclear cells (PBMCs) with MDSCs derived from HCV‐infected patients or treated with HCV core protein. In addition, depletion of MDSCs from PBMCs led to a significant reduction of Foxp3 + Treg cells developed during chronic HCV infection. Moreover, depletion of MDSCs from PBMCs significantly increased interferon‐ γ production by CD4 + T effector (Teff) cells derived from HCV patients. These results suggest that HCV‐induced MDSCs promote Treg cell development and inhibit Teff cell function, suggesting a novel mechanism for T‐cell regulation and a new strategy for immunotherapy against human viral diseases. Abstract : In this study, we demonstrated: i) an expansion of M‐MDSCs in patients with chronic HCV infection; ii) HCV‐induced M‐MDSCs express high levels of pSTAT3 and IL‐10 compared to healthy subjects; iii) HCV‐induced MDSCs promote Treg cell development and inhibit Teff cell function.